Reformas a la ley orgánica de participación ciudadana para garantizar el cumplimiento de la silla vacía en las sesiones de los gobiernos autónomos descentralizados. - CUENCA ALVARADO, LUIS ALFREDO (2012)
The subject is mainly base on the need to demand to autonomous de-centralised Govenrments, the application of empty chair tool, without much delay and to safeguard the constitutional right of the citizens individual and collective,that are violating in a inexcusable way, like pretence of the lack of validity of it. When investigating this topic, you detect, something like don't care, to the lack of knowledge of the current laws on the autonomous Governments Decentralized, on the Civic participation where the 2008 constitution recognize "In Government's levels they conformed to participation request integrated by authorities elect representatives of the dependent Régime and representatives of the Society of the Territorial environment of Government's level. The theoretical work and of field of the present thesis I allow myself to obtain approaches, with clear and precise foundations of bibliography, very grateful that contributed to the verification of the objectives and recruiting of outlined hypothesis, allowing to support the proposed changes. The content of the thesis is an intellectual effort of the petitioner in the scientific environment and, methodological that approaches theoretical and empirically, the limitation to the fundamental right of the Civic participation; in view of the ability that it grants him the organic code and classification territorial Autonomy and Decentralization that it involves the citizen and citizen in elaborating plans and political national, local and sectoral between the Governments and the citizenship and for consequence the use of the Empty Seat in the sessions of the Municipal Decentralized Autonomous Governments.